If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4 + -5a = 4(1 + 8a) 4 + -5a = (1 * 4 + 8a * 4) 4 + -5a = (4 + 32a) Add '-4' to each side of the equation. 4 + -4 + -5a = 4 + -4 + 32a Combine like terms: 4 + -4 = 0 0 + -5a = 4 + -4 + 32a -5a = 4 + -4 + 32a Combine like terms: 4 + -4 = 0 -5a = 0 + 32a -5a = 32a Solving -5a = 32a Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '-32a' to each side of the equation. -5a + -32a = 32a + -32a Combine like terms: -5a + -32a = -37a -37a = 32a + -32a Combine like terms: 32a + -32a = 0 -37a = 0 Divide each side by '-37'. a = 0 Simplifying a = 0
| 4x^2^4-16x^4/12ux^5 | | 45/17 | | 7r+5=11 | | V=3812 | | X-6-20=142 | | 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= | | r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 | | 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d | | 1/3x-8=4/9x | | 20=a/9 | | 26=13/v | | -7(3a-2)+4(5a+5)= | | 10=6+(1+3m)-2(2+10m) |